KINERJA APARATUR SIPIL NEGARA DINAS KOPERASI UKM TRANSMIGRASI DAN TENAGA KERJA KABUPATEN ROKAN HULU (STUDI KASUS PENERAPAN PERATURAN BUPATI NO.18 TAHUN 2011) - Afni, Nur; Harahap, Tuti Kahirani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The purpose of this research is to know how the performance of State Civil Service Apparatus Office of Dinas Koperasi UKM Transmigrasi Dan Tenaga Kerja Kabupaten Rokan Hulu (Case Study of Regent Regulation No.18 of 2011) and to To know the factors that affect the performance of Civil State Apparatus Office of Dinas Koperasi UKM Transmigrasi Dan Tenaga Kerja Kabupaten Rokan Hulu (Case Study of Regent Regulation No.18 of 2011). Data analysis method used in this research adlah descriptive qualitative analysis method. Data collection technique in accordance with the problems faced by this problem is done data collection techniques in the form of interew, observation and documentation on the main and additional information. Based on the results of the discussions that have been described on the performance of the worker running maximally it has been trying to carry out its main duties correctly even though there is an indication that it has not been optimally caused by the implementation policy which resulted in employees not having more time than before in serving the community.Keywords: Employee Performance, Regent Regulation